Literature Review of Capital Intensity , Leverage , and Liquidity With Profitability as Moderating Variables on Tax Aggressiveness - Cris Kuntadi; Syahdilla Aulia Rahman; Rachmat Pramukty (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2025)
Taxes have long been one of the requirements for realizing national development. From these taxes, facilities, means, and other objects are built as access to facilitate sustainable economic development. The results obtained from taxes will be used as well as possible for the welfare of the people. Tax revenues can run optimally if all people pay taxes. However, in reality there are many factors that motivate someone to understand their obligations in paying taxes. The purpose of writing this article is to analyze and examine the effect of capital intensity, leverage, and liquidity on tax aggressiveness with profitability as a moderating variable . The method used in this literature review is the library research method sourced from online media such as Google Scholar, Mendeley, and literature studies. The results obtained from this literature review article are: 1) capital intensity has a positive effect on tax aggressiveness. 2) leverage has a positive effect on tax aggressiveness. 3) liquidity has a negative effect on tax aggressiveness; 4) profitability can moderate the effect of capital intensity, leverage, and liquidity on tax aggressiveness.